Unpacking Qualitative Methodology to Explore Experiences of Mothers with Children with Autism Spectrum Disorder in the UAE: A Thematic Analysis Inquiry. (20th June 2022) - Lamba, Nishtha; Van Tonder, Angelique; Raghavan, Archana
The current study provides a detailed description of the qualitative research design and methodology, used while exploring challenges and support structures experienced by expat mothers of children with Autism Spectrum Disorder (ASD) in the United Arab Emirates. In-depth, face-to-face, semi-structured interviews were administered with 17 mothers recruited using purposive and snowball sampling. Recurrent and relevant themes were generated using thematic analysis. Given there is a greater need for highlighting methodological rigor in qualitative research, we discuss steps such as a) using field knowledge to create an interview protocol, b) administering collaborative qualitative research, c) having strong eligibility criteria for participants, d) incorporating perspectives of multiple coders in the analytical process, e) being reflective and aware of one's potential biases, f) enhancing interview protocol based on pilot interviews, g) and focusing on the quality of perspectives or information power instead of quantity of perspectives. Interpretation of findings and recommendation of evidence-informed guidelines incorporates strengths and limitations of the qualitative methodology utilized in the study.